2014
DOI: 10.5468/ogs.2014.57.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal adhesions in a woman with the history of dystocia

Abstract: Postpartum genital tract adhesions are unusual, and their cause has not been evaluated. However, severe dystocia and numerous pelvic examinations have been suggested as possible causes. Here, we report a case of vaginal adhesions following a difficult labor that presented as dyspareunia for 5 months. Pelvic examination and ultrasonography revealed a transverse vaginal septum that obstructed the vaginal cavity, and fluid collection proximal to this septum. The patient was successfully treated with surgical rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…4 Extensive perineal injuries in childbirth and multiple examinations, may also cause vaginal adhesions. 5 Our case of vaginal atresia with tuberculosis appears to be unique. The diagnosis of tuberculosis leading to vaginal atresia should be considered in episiotomy wound or vaginal lacerations, especially in areas where tuberculosis is endemic.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…4 Extensive perineal injuries in childbirth and multiple examinations, may also cause vaginal adhesions. 5 Our case of vaginal atresia with tuberculosis appears to be unique. The diagnosis of tuberculosis leading to vaginal atresia should be considered in episiotomy wound or vaginal lacerations, especially in areas where tuberculosis is endemic.…”
Section: Discussionmentioning
confidence: 75%
“…4 Extensive perineal injuries in childbirth and multiple examinations, may also cause vaginal adhesions. 5…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that genital tract trauma such as large vulvar oedema, or vaginal or labial laceration is associated with postpartum labial adhesions. 3,5 Strangely, our case presented as actual obstruction of the vaginal canal. Kamal et al in 2010 presents a case of pinhole vagina following vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Labial adhesions, or actual adhesions of the vaginal cavity, are uncommon in reproductive-aged women. 3 However, a vaginal technique cannot be used to remove mid-and high vaginal stenosis without causing harm to the surrounding structures. 4 Traditional treatment involves an abdomino-perineal approach that necessitates a laparotomy.…”
Section: Introductionmentioning
confidence: 99%